Rural Renovation in les Landes, South West France : A French Regional Development Experiment - Ironstone, R. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1968)
Regional planning is an important item of government policy in France, and the rural land management of the Landes in the Aquitaine region offers a good example. The factors which instigated this planning operation were the constant rate of decrease in the areas under forest and of agricultural land, the decline in economic activity in an area where the natural environment is not very favourable and the exodus of the population. Numerous measures have been taken to improve the level of the economy in this region. In 1965, la Compagnie d'aménagement des Landes de Gascogne was established; its main objective is to protect the forest from destruction by creating enclaves of subsistence agriculture, which serve as fire breaks and at the same time reactivate the economy. La Compagnie d'aménagement des Landes de Gascogne aims there fore at stabilizing the region once again by setting up new activities. The arable land has been re-divided and transport, drainage and irrigation equipment, capable of attracting labour, is being installed. The planning organization has partially attained the goals that were set. The area of forest devastated by fire has been reduced more and more, and agricultural returns are higher. On a long term basis, the application of this plan of land management in the rural areas of Aquitaine is proving a success.